Prospect of Natural Killer Cells in Cancer Imunotherapy - Anna Meiliana; Nurrani Mustika Dewi; Andi Wijaya (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Current understanding in molecular character of natural killer (NK) cell, its function and mechanisms, send people the ideas to develop a NK cell-based immunotherapeutic strategies against human cancer.CONTENT: Before being regards as a cell-based cellular therapy, NK cell have to be clinical proven. Early studies with NK cells infusions for acute myeloid leukemia and lung cancer showed a promising result. NK cells need simplified methods for enriching and expanding, in addition to its transfection with chimeric antigen receptors (CARs). NK-92 arise as an assuring effector cells to augment monoclonal and bispecific antibody therapy. Thus, NK cells show a potential opportunity for cell engineering, outstep the era of T cells.SUMMARY: It is believed that NK cells bring a bright hope for future cancer immunotherapies, either alone or in combination as a harmonious therapy.KEYWORDS: NK cells, NK-92 cells, immunotherapy, CAR